To the question on vaccination of pregnant women during COVID-19 pandemic - E. Yu. Yupatov; L. I. Maltseva; N. Z. Yusupova; L. Z. Safina; E. G. Ignashina; T. E. Kurmanbaev; K. M. Atayants; A. A. Shmidt (IRBIS LLC, 2020)
The pandemic of the novel coronavirus disease 2019 (COVID-19) makes us to think about effective preventive methods in pregnant women, because the course of such infection is accompanied by a high risk of severe endotheliopathy, disseminated intravascular coagulation, septic shock, thromboembolic complications and maternal mortality. Undoubtedly, vaccination is the most effective method of protection during pandemic, which experience in some infections in pregnant women has been accumulated in the world practice and may be also used for the COVID-19 vaccine. Here we discuss the issues of vaccination for pregnant women to expand the view of medical doctors and eliminate prejudice against immunization of pregnant women.